A comprehensive prediction model for vehicle/track/soil dynamic response due to wheel flats. (May 2016) - Alexandrou, Georgios; Kouroussis, Georges; Verlinden, Olivier
With the development of new lines and the increase of traffic on existing lines, the problem caused by railway-induced ground vibrations is becoming bigger and bigger. The present paper focuses on wheel flat modelling in prediction schemes which determine railway-induced ground vibrations and which have applications to urban tramways. A comprehensive flat spot model is developed and included in an existing vehicle/track model taking into account Hertz's contact law. The associated non-linear stiffness is calculated in a pre-processing step by solving the three-dimensional wheel/rail contact problem. A two-step approach for predicting ground vibrations, developed by the authors, is then applied, including the track/soil interaction through a foundation model and the ground wave propagation by means of a fully three-dimensional finite element model. Predicted results are presented, based on the T2006 tram and on the railway site of Haren (Belgium). A specific analysis is proposed for studying the vehicle dynamics on flexible tracks, and for calculating the effect provided by the wheel flat impact on the rail heads. Results related to the contact force between the wheel with a flat spot and the rail are presented. A series of periodic impacts are generated when the flat spot comes into contact with the rail head with magnitude depending on the track flexibility at the contact point. The key conclusions are discussed, based on the sensitivity analysis of the flat spot size and the train speed. Both parameters affect the critical speed of the vehicle/track system, defined as the speed where loss of contact occurs. The ground vibration levels were found to increase with speed and decrease with distance.